Efektivitas Proses Komunikasi Interpersonal Antara Pembina Dengan Anak Asuhnya di Sanggar Merah Merdeka Surabaya - Hilda Yunita Wono (Kanal: Jurnal Ilmu Komunikasi, 2019)
Researchers want to know that is not happen in the process interpersonal communication as well as improvement interpersonal communication between shelter comitee and foster kids in the Sanggar Merah Merdeka, which ultimately determine the achievement of the shelter's goals. This study uses quantitative descriptive methods that are used to describe and analyze social events and activities, as well as beliefs, attitudes, perceptions, and thoughts individually or in groups to get a picture of the effectiveness of interpersonal communication carried out in daily life between the comitee of the "Sanggar Belajar Merah Merdeka" with his foster kids. Based on research results. messages according to the purpose of the studio, communication channels, communicant, interference, feedback in the shelter activities daily. Nothing to miss about demonstrates openness, empathy, communication supporting attitudes, positive attitudes, and equality also always emerge.